2008
DOI: 10.1002/ijc.23207
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species‐dependent destruction of MEK and Akt in Manumycin stimulated death of lymphoid tumor and myeloma cell lines

Abstract: Manumycin-A (Man-A) is a farnesyltransferase inhibitor (FTI), which was originally identified as an effective tumoricide against several cancers, especially ones harboring constitutively active Ras. However, it is becoming apparent that Man-A can stimulate tumor death independently of FTases. Antioxidant treatment blocked Man-A-stimulated DNA damage and reversed Man-Ainhibited tumor growth. However, the precise molecular details of how these reactive oxygen species (ROS) influence cell signaling modules are po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Recently, the anti-neoplastic activity of Manu A has been demonstrated in various experimental systems (18). It exerts antitumor activity against a variety of cancer cells such as human pancreatic cancer cells (19), anaplastic thyroid cancer cells (20,21), human colon tumor cells (22) and human hepatocellular carcinoma HepG2 cells (23), medulloblastoma cells (24,25), leukemic cells (26), lymphoid tumor and myeloma cell lines (27,28). However, little is known concerning the anticancer mechanisms of Manu A by which it can induce apoptosis in MPM cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the anti-neoplastic activity of Manu A has been demonstrated in various experimental systems (18). It exerts antitumor activity against a variety of cancer cells such as human pancreatic cancer cells (19), anaplastic thyroid cancer cells (20,21), human colon tumor cells (22) and human hepatocellular carcinoma HepG2 cells (23), medulloblastoma cells (24,25), leukemic cells (26), lymphoid tumor and myeloma cell lines (27,28). However, little is known concerning the anticancer mechanisms of Manu A by which it can induce apoptosis in MPM cells.…”
Section: Introductionmentioning
confidence: 99%
“…Even though inhibition of farnesyltransferase may account for the antiproliferative effects of manumycins, recent data indicate that manumycins induce tumor cell death independently of farnesyltransferase and inhibition of ras signal transduction pathways (21). Manumycin-induced apoptosis in tumor cells has been shown by measuring various parameters including release of mitochondrial cytochrome c into the cytosol, activation of caspases 8, 9 and 3, as well as increased DNA fragmentation (6,7,9,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Manumycin-induced apoptosis in tumor cells has been shown by measuring various parameters including release of mitochondrial cytochrome c into the cytosol, activation of caspases 8, 9 and 3, as well as increased DNA fragmentation (6,7,9,21,22). She et al (7) suggested that the cellular death induced by manumycin in human thyroid cancer cells fits the general pattern of xenobiotic-induced apoptosis, which is characterized by induction of oxidative stress, MAPK signaling (p38 MAPK in particular), release of cytochrome c and subsequent activation of the apoptotic pathways (reviewed in ref.…”
Section: Discussionmentioning
confidence: 99%
“…(Karp and Lancet, 2005;Santucci et al, 2003). Manumycin (Man)-A induces apoptosis in B-c e l l t u m o r s b y i n h i biting prenylation (Frassanito et al, 2002) and also by generating ROS that inhibits Ras/MEK/ERK and Ras/PI3K/Akt pathways by cleaving MEK and Akt (Sears et al, 2008). R115777 (zarnestra/tipifarnib) is a FTI that has shown promising clinical results in acute myeloid leukemia, myelodysplastic syndromes, chronic myelogenous leukemia, and MM and with anti-tumor effects noted independent of Ras mutations (Martinelli et al, 2008).…”
Section: Arsenic Trioxide (Ato)-preclinical Data Shows Ato Activity Imentioning
confidence: 99%